Understanding the Meaning of “Project Success” - Goparaju Purna Sudhakar (Binus Business Review, 2016)
Fortune 500 organizations are executing their tasks using projects. Project management is the area of concentration across the world. Different stakeholders have a different perspective about project success. The meaning of project success had been explained in this article. In addition, the Project Critical Success Factors (CSFs) were mentioned. The research of Standish Group on project success and project success metrics was presented. Earlier research on the meaning of project success and project critical success factors was highlighted. The works of Jeffery K. Pinto and Dennis P. Slevin, David and Adam, DeLone and McLean, and The Standish Group Research were discussed in this article. The methodology included secondary research based on literature view of prominent empirical studies and the literature reviews by making note of findings and observations from those studies. The initial literature collected led to further search of articles based on their references. The research findings indicate that the top of the most success factors for many projects include project objective, top management commitment, competent project team, and user involvement.